Blood treatment of Lyme borreliae demonstrates the mechanism of CspZ‐mediated complement evasion to promote systemic infection in vertebrate hosts. (7th January 2019) - Marcinkiewicz, Ashley L.; Dupuis, Alan P.; Zamba‐Campero, Maxime; Nowak, Nancy; Kraiczy, Peter; Ram, Sanjay; Kramer, Laura D.; Lin, Yi‐Pin
Abstract: Lyme disease, caused by the spirochete Borrelia burgdorferi, is the most common vector‐borne disease in the United States and Europe. The spirochetes are transmitted from mammalian and avian reservoir hosts to humans via ticks. Following tick bites, spirochetes colonize the host skin and then disseminate haematogenously to various organs, a process that requires this pathogen to evade host complement, an innate immune defence system. CspZ, a spirochete surface protein, facilitates resistance to complement‐mediated killing in vitro by binding to the complement regulator, factor H (FH). Low expression levels of CspZ in spirochetes cultivated in vitro or during initiation of infection in vivo have been a major hurdle in delineating the role of this protein in pathogenesis. Here, we show that treatment of B. burgdorferi with human blood induces CspZ production and enhances resistance to complement. By contrast, a cspZ ‐deficient mutant and a strain that expressed an FH‐nonbinding CspZ variant were impaired in their ability to cause bacteraemia and colonize tissues of mice or quail; virulence of these mutants was however restored in complement C3‐deficient mice. These novel findings suggest that FH binding to CspZ facilitates B. burgdorferi complement evasion in vivo and promotes systemic infection in vertebrate hosts.